Roles of Dermcidin, Salusin-?, Salusin-? and TNF-? in the Pathogenesis of Human Brucellosis - Tartar, Ayse Sagmak; Balin, Safak Ozer; Akbulut, Ayhan; Yardim, Meltem; Aydin, Suleyman (Shiraz Inst Cancer Res, 2019)
Background: Brucella spp. are facultative intracellular pathogens that can cause chronic infections in many tissues and organs. Objectives: To investigate serum dermcidin, salusin-alpha, salusin-beta and TNF-alpha levels and their correlation with each other in patients with acute brucellosis. Methods: From 50 patients hospitalized upon diagnosis of acute brucellosis, blood samples were collected and dermcidin, salusin-alpha, salusin-beta and TNF-alpha levels in serum samples were measured using an ELISA assay. The control group included 40 volunteers. Results: Brucellosis group had significantly lower plasma dermcidin, salusin-alpha, salusin-beta levels compared to the healthy control group (respectively p:0.008, p<0.001, p<0.001). Moreover, Brucellosis group had significantly higher plasma TNF-alpha levels comparisons with the controls (p=0.002). In the examination of the correlation between TNF-alpha and dermcidin, salusin-alpha and salusin-beta in the brucellosis group, only a negative correlation was found between salusin-beta and TNF-alpha. In the control group, there was a positive and statistically significant correlation between salusin-beta and TNF-alpha. Conclusion: Dermcidin, salusin-alpha, and, particularly salusin-beta levels are important in Brucella pathogenesis. The paradoxical correlation between TNF-alpha and salusin-beta in patients with brucellosis and control group is remarkable. However, there is a need for extensive studies conducted with more patients to further elucidate this topic.
Keywords: Brucellosis; Dermcidin; Salusin-Alpha; Salusin-Beta; TNF-Alpha